Motivation for Domestic Tourists to Visit Sayan Tourism Village, Gianyar Regency - Thariana, Putu Lisa; Tirtawati, Ni Made; Mertha, I Wayan (Indonesian Journal of Applied and Industrial Sciences (ESA), 2024)
The purpose of this study was to determine the push motivation and pull motivation factors of domestic tourists visiting Sayan Tourism Village, Gianyar Regency. The population of this study were domestic tourists who had visited Sayan Tourism Village, Gianyar Regency. Using the Yamane formula, a total of 100 respondents were obtained with the Purposive Sampling technique, followed by sampling using Accidental Sampling. Data collection was carried out using survey methods (questionnaires), observation and literature studies. The collected data were analyzed using Exploratory Factor Analysis (EFA) with the SPSS 25 application program. The results showed that 5 new push factors were formed from 24 indicators. The push factors are: cultural exploration and vacation factors; breaking away from routine; relaxation; pride; and nostalgia. The pull factors derived from 21 indicators formed 5 new factors, namely: first, cultural attraction factor; second, natural attraction factor; third, tourism facility factor; fourth, accessibility pull factor; and finally, destination image factor. The dominant factors of the push factors are cultural exploration and vacationing, while the dominant factor of the pull factors is cultural attraction.